Acta dermatovenerologica Alpina, Pannonica et Adriatica at the occasion of 10th anniversary - Kansky, Aleksej (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2002)
The dermatological journal the ACTA DERMATOVENEROLOGICAALPINA, Pannonica etAadriatica (Acta Dermatoven APA) has in fact a 28-year history. In 1974 J. Fettich and S. Bunta have started the Yugoslav dermatological journal (Acta derm lug), which appeared during 18 years, four times yearly in Serbian and Croat languages. After the outbreak of civil war in former Yugoslavia it became clear that in this shape the journal had no future. The then Chief Editor A. Kansky transferred the Editorial office from Zagreb to Ljubljana, renewed the registration under a more suitable name corresponding to the changed political situation and assigned to the journal a broader field of activities: additionally to the exchange of information it should induce and help the authors to prepare their manuscript according to international standards and to use strictly the English language. With the help of prominentcolleagues from Ljubljana, Maribor, Graz, Trieste as well as others, the Acta Dermatoven APA started to appear in 1992 in Ljubljana, four issues yearly. The Editors had to cope with many problems, they managed however to survive and to enter into its 11 th year of existence. The journal was financially supported by the then Ministry of Science and Technology of Slovenia as well as by advertisements, mostly from pharmaceutical companies. In 1994 the journal was accepted into the information basis of EMBASE/ExcerptaMedica and Biomedicina Slovenica. The Editors made efforts in 1993 and again in 1998 to be accepted into the information basis of Index Medicus and Current Contents, but did not succeed. They were however able to attract authors contributing manuscripts and readers in Southeastern Europe and in former socialist countries. Changes in the Editorial Office which are planned, are expected to exert an even stronger impact in affirmation of the journal.
Keywords: Acta dermatovenerologica Alpina, Pannonica et Adriatica (periodika); Dermatologija; Dermatology; Periodicals; Periodika; Pisanje; Trends; Writing